The Effectiveness of Blended Learning Assisted by Collaboration of Edmodo Probing-Prompting in Improving Learning Outcomes and Critical Thinking Ability of Students at Universitas Madura - Mustakim; Agung Haryono; Sunaryanto (CV. AFDIFAL MAJU BERKAH, 2022)
Technological developments have a positive impact on education. Students are required to have knowledge and skills as a result of learning. However, the results of teaching and learning conducted at the University of Madura have not achieved the expected learning objectives. The purpose of the study was to determine the effectiveness of blended learning assisted by probing-prompting Edmodo collaboration in improving learning outcomes and critical thinking skills. This research is quasi-experimental with a 2x2 factorial design. Determination of the sample using random sampling from 4 odd-even classes with a total of 65 students majoring in Accounting at the University of Madura. Data collection techniques used pretest-posttest with the help of the IBM Statistics-24 application. The normality test used one-sample Kolmogorov-Smirnov and the homogeneity test used Levene with a significance of 5%. Hypothesis testing with two-way analysis of variance based on a 2x2 factorial design. The research data showed an increase in learning outcomes and critical thinking skills in the BLPP class from pretest to post-test was 0.39 and 0.80 with a total of 1.19 percent. While the PPF2F class increased from pretest to post-test by 0.42 and 0.63 with a total of 1.05 percent. Based on the results of the research data analysis, it was concluded that the blended learning model assisted by the probing-prompting collaboration Edmodo was effective in improving student learning outcomes and critical thinking skills in introductory accounting courses. The increase obtained in addition to internal factors is also due to the advantages that exist in the BLPP. Therefore, the selection of models and approaches used is one of the determinants of achieving learning objectives. So, the BLPP model is a learning model that can influence improving learning outcomes and critical thinking skills.